MODELLING MITIGASI PAPARAN (EXPOSURE) MEDAN LISTRIK MELALUI INOVASI PENGGUNAAN KISI-KISI KAWAT GROUNDING DAN TANAMAN RAMBAT BERBUNGA - utama, Budi (ReTII, 2021)
ABSTRACT The reduction of the intensity of the electric field exposure under the Extra High Voltage Transmission Lines was carried out by modifying the Maxwell Potential Coefficient Matrix modelling at condition the "with and without" ground wire which was grounded and stretched parallel to the stretch of the phase conductor. The development through the innovation of this single ground wire into a grid, which was placed under the EHV Transmission Lines, reduced the exposure the intensity of the electric field under the EHV Transmission Lines. The modelling method carried out by solving the electrostatic equation for each phase conductor which also accompanied by a ground wire which was stretched under the EHV Transmission Lines with a certain height above the ground surface. The single grounding wire were formed into the gratings wire. The results of this innovation can be used for houses that located under the EHV Transmission Lines route where the top of the gratings wire can also be added with types of vines/flowering plants that can be increased aesthetic aspects. Keyword : Modelling, Mitigation, Electric-Field, Innovation.